Greetings from Brasil...
The equation is:
COS X - √(1 - 3.COS² X) = 0
putting COS X for the 2nd member
- √(1 - 3.COS² X) = - COS X ×(- 1)
√(1 - 3.COS² X) = COS X everything squared
[√(1 - 3.COS² X)]² = (COS X)²
1 - 3.COS² X = COS² X
1 - 3.COS² X - COS² X = 0
1 - 4.COS² X = 0
making Y = COS X
1 - 4Y² = 0
- 4Y² = - 1 ×(- 1)
4Y² = 1
Y² = 1/4
Y = ±√1/4
Y = ± 1/2
so, as we saw above
Y = COS X
1/2 = COS X and - 1/2 = COS X
so to get COS X = ± 1/2, then
X = π/3 = 60 (cos +)
X = 2π/3 = 120 (cos -)
X = 4π/3 = 240 (cos -)
X = 5π/3 = 300 (cos +)
So the only option that includes + and - its:
60° + n360° , 120° + n360°